2012
DOI: 10.1186/1475-2859-11-159
|View full text |Cite
|
Sign up to set email alerts
|

The hemicellulolytic enzyme arsenal of Thermobacillus xylanilyticus depends on the composition of biomass used for growth

Abstract: BackgroundThermobacillus xylanilyticus is a thermophilic and highly xylanolytic bacterium. It produces robust and stable enzymes, including glycoside hydrolases and esterases, which are of special interest for the development of integrated biorefineries. To investigate the strategies used by T. xylanilyticus to fractionate plant cell walls, two agricultural by-products, wheat bran and straw (which differ in their chemical composition and tissue organization), were used in this study and compared with glucose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…The state of crystallinity of the fibers in a cellulosic biomass indicates the hydrolytic capacity of the material, this being the main focus of the studies in the second-generation ethanol industries. The lignin content of the flower stalk was relatively low, and according to Masarin et al [39] it can be considered a desirable concentration as under mild pretreatment conditions the extraction of this component is disregarded, and the process proceeds to the subsequent step of sugar extraction from the cellulosic material [40]. The lignin content of the flower stalk was relatively low, and according to Masarin et al [39] it can be considered a desirable concentration as under mild pretreatment conditions the extraction of this component is disregarded, and the process proceeds to the subsequent step of sugar extraction from the cellulosic material [40].…”
Section: Chemical Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…The state of crystallinity of the fibers in a cellulosic biomass indicates the hydrolytic capacity of the material, this being the main focus of the studies in the second-generation ethanol industries. The lignin content of the flower stalk was relatively low, and according to Masarin et al [39] it can be considered a desirable concentration as under mild pretreatment conditions the extraction of this component is disregarded, and the process proceeds to the subsequent step of sugar extraction from the cellulosic material [40]. The lignin content of the flower stalk was relatively low, and according to Masarin et al [39] it can be considered a desirable concentration as under mild pretreatment conditions the extraction of this component is disregarded, and the process proceeds to the subsequent step of sugar extraction from the cellulosic material [40].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…These temperatures can be applied to both physical and electrical pretreatments, such as ultrasound power [43] and pulsed electric current [11], where cooling systems must be used to avoid the production of fermentation inhibitors in the aqueous biomass. Thus, cellulose degradation is one of the most important processes in the carbon cycle, normally involving the combined action of several synergistically functioning enzymes [19,40,44]. In the pH range studied, the use of mildly acid concentrations maintains the degree of crystallinity of the cellulose, and hence allowing for better enzymatic hydrolysis as a possible combined pretreatment application.…”
Section: The Specific Heat Capacity Of the Flower Stalk Powder In Aqumentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Similarly, it was suggested that the growth of Thermobacillus xylanilyticus on lignocellulosic materials promoted the extracellular accumulation of proteins and simple sugars during the exponential growth phase, which extended the viability of the microorganism as well as a low degree of sporulation [Rakotoarivonina et al, 2012]. These findings might also be related to the result of a physiological adaptation to complex microbial niches related to lignocellulosic recycling in nature.…”
Section: Discussionmentioning
confidence: 95%
“…3 ). The usefulness of feedstocks for enzyme production was also reported for members of the Paenibacillaceae family [Arora et al, 2014;Rakotoarivonina et al, 2012]. Cohnella sp.…”
Section: Discussionmentioning
confidence: 99%